Construction and testing of a substitute resistance box for high school physics - Ballesteros, Elisa P. (Animo Repository, 1978)
This study constructs a substitute resistance box for high school Physics comparable to a resistance box imported from a reputable company producing standard science apparatus and equipment. With this improvised resistance box made out of locally available materials produced at very low cost, one of the highly-priced and expensive equipment could be used in ordinary experiments in electricity. To get good results, the resistance boxes have to be calibrated first before experimenting. Calibrated resistance boxes were found to work well and produce good results similar with that of the standard resistance decade box. Results of the experiments on Ohm's Law and Resistors in Series and Parallel showed the following using the t-test of difference between means for uncorrelated samples: 1) For indicated values of resistances using the improvised resistance box: a) There is no significant difference between the means of the experimental errors in obtaining the voltage, V in Ohm's Law experiment at 5 percent and 1 percent levels of significance. b) There is no significant difference between the means of the experimental errors in obtaining the total resistance, R of resistors in series and total voltage, V, of resistors in parallel at 5 percent and 1 percent levels of significance. 2) For calibrated values of resistances using the improvised resistance box: a) All experiments performed showed that there is no significant difference between means of the experimental errors at 5 percent and 1 percent levels of significance. b) Computed variances for calibrated values of resistances for an improvised resistance box and standard resistance decade box showed no exact trend in increase in variances. These proved therefore that errors may be attributed to some other factors other than the apparatus itself.